(untitled) (International Seven Journal of Multidisciplinary, 2023)
Biodiesel is an alternative fuel obtained from natural and renewable sources, with several advantages over regular diesel. The objective of this work was to extract biodiesel from extra virgin Chia oil and analyze different diesel blends obtained. The method for carrying out this process was by transesterification of Chia extra virgin oil, with methanol and a catalyst (sodium hydroxide), at a temperature of 60°C, for 1 hour. Analysis of the biodiesel obtained. The results of the biodiesel obtained showed a chemical composition suitable for use as fuel. The most efficient mixture was the one containing 20% biodiesel and 80% ordinary diesel. In this sense, it is concluded that Chia extra virgin oil can be used as a source of biodiesel due to its suitable chemical composition. The blend of 20% biodiesel and 80% ordinary diesel was the most efficient in terms of emission of pollutant gases.